Lecture of Calculus 2 = Bài giảng môn Giải tích 2 - Nguyễn Hữu Thọ (Trường Đại học Thuỷ Lợi, 2020)
Contents: Intergration by part. Partial fractions; Trigonometric Integrals. Improper integrals; Area of the regions between curves; Volumes. Lengths of Plane Curves. Areas of Surfaces of Revolution; Physical applications: Moments and Centers of Mass; Infinite Series; Integral test. Comparison ,Ratio and Root tests; Alternating series; Power series. Taylor and Maclaurin series; Covergence of Taylor series. Application of power series; Parametric equations. Polar corrdinates; An introduction to matrices